Effects of uniaxial stress on dielectric properties of 0.9PMN-0.1PT ceramics - Triamnak N. (2014)
This study deals with the influence of uniaxial stress on the dielectric properties of electrostrictive PMN-PT ceramic. The dielectric properties of lead magnesium niobate-lead titanate prepared by a mixed-oxide method with composition ratio 9:1 were measured under uniaxial compressive stress up to 22 MPa. The experimental results revealed that the superimposed compression load significantly reduced both the dielectric constant and the dielectric loss tangent in every measuring frequency. The observations were interpreted in terms of clamping of domain walls and de-poling under the compressive loading. The change of the dielectric properties with stress was attributed to competing influences of the intrinsic contribution of non-polar matrix and the extrinsic contribution of re-polarization and growth of micro-polar regions. In addition, the results reported here also suggested a significant influence of the experimental conditions on the uniaxial stress dependence of dielectric properties of the PMN-PT ceramic. © 2007 Springer Science+Business Media, LLC.